Estudio del tratamiento de la información publicada sobre los casos de violencia de género en la ciudad de Loja, a través de los periódicos La Hora, La Crónica, en el periodo diciembre 2017- mayo 2018 - Cabrera Erreyes, Verónica Jhulissa (2020)
The research is based on the analysis of the informative treatment that the news of gender violence received in the period December 2017 to May 2018, in the printed media of Loja such as La Hora and La Crónica. This study was born from cases of gender violence and femicide that occurred in the city, which caused a great commotion, and the interest of knowing how local print media focused the information. Gender violence is a social problem that has been increasing and that despite the existence of laws, few have been solutions. From gender violence, femicide is born the last link of violence. The media played an important role as trainers of public opinion when spreading news related to violence. With an analysis of agenda-setting and framing (framing) to the published notes, the information collected allowed us to identify that the informative treatment was not the most appropriate since in repeated notes the facts were described morbidly, finding errors in the speech. The main actors were the authorities giving most news a legal or police approach and not rights, feminist groups had little space compared to the authorities. For what has already been described, an alternative proposal is proposed, which is the creation of a decalogue of good journalistic practices for the informative treatment in cases of gender violence, which is addressed to journalists of the media, to respond to gender violence news responsibly.